2018
DOI: 10.2478/bjdm-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Oral lipoma located at the left lower vestibule-report of a case and a brief review of the literature

Abstract: Summary Backround/Aim: The present paper focuses on examining a case report of an oral lipoma located at the left lower vestibule. Case report: The patient’s clinical state was thoroughly studied, along with the findings of histopathological examinations. The surgical treatment and postoperative course are also within the scope of this report. Numerous histogenesis theories and the appropriate tumor treatment are mentioned within the article, being always in accordance with the relative literature. Conclusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…There are different reports about the relationship between lipoma and sex. The incidence of oral lipoma has been reported to be identical in the males and females, or male prevalence has been emphasized or vice versa …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different reports about the relationship between lipoma and sex. The incidence of oral lipoma has been reported to be identical in the males and females, or male prevalence has been emphasized or vice versa …”
Section: Discussionmentioning
confidence: 99%
“…The incidence of oral lipoma has been reported to be identical in the males and females, or male prevalence has been emphasized or vice versa. 21 Bone lesions are often discovered by accident. Radiographic images show unilocular or multilocular radiolucent lesions with a honeycomb or soap bubble appearance and often an osteosclerotic border.…”
Section: Discussionmentioning
confidence: 99%
“…5 While the site predilection is still under consideration, it has been hypothesised that this is related to the availability of adipose tissue, which would explain the high incidence in the buccal mucosa due to the proximity to the buccal fat pad. 6 Lipomas of the tongue represent only 0.3% of all tongue neoplasia 5,7,8 and these are rare as the tongue is usually totally devoid of any fat cells. While Naruse et al (2014) reported that tongue lipomas account for 16.6% of all oral lipomas, a more recent study by Osterne et al (2019) recorded a lower prevalence of tongue lipomas, accounting for 6.93% of oral lipomas.…”
Section: Discussionmentioning
confidence: 99%